Si as dopant impurity in CdTe - Fochuk, P.M.; Panchuk, O.E. (Functional Materials, 2005)
CdTe<Si> single crystals have been investigated by high-temperature Hall effect meas- urements under Cd vapor pressure in 200-900 ℃ temperature range. Basing on the experimental results, the Si solubility in CdTe at 500-600 ℃ has been supposed to be lower than ≈ 3*10¹⁶ at/cm . The Si segregation coefficient in CdTe is exceeds unity (kₛₑᵣᵍ > 1). This peculiarity of Si behavior in CdTe differs it from other IVA group elements. At high Si content in CdTe (~ 10¹⁷ at/cm³), it is mainly contained in precipitates. Their dissolution starts at Т ~ 500 ℃ and the subsequent cooling does not reduce the concentration of
electrically active Si form. The dominating Si point defect is Si+ᶜᵈ , although a certain
fraction of this impurity forms associates (Si+ᶜᵈ V²⁻ᶜᵈ ). Монокристали CdTe<Si> дослiджено вимiрюваннями ефекту Холла пiд тиском пари Cd в iнтервалi температур 200-900 ℃. На основi експериментальних даних припущено, що розчиннiсть Si менша за ~ 3*10¹⁶ ат/см³ at 500-600 ℃. Коефiцiєнт розподiлу Si у CdTe бiльший за одиницю (kₛₑᵣᵍ > 1), що вiдрiзняє його вiд iнших елементiв IVA пiдгрупи елементiв. При високому вмiстi Si (~ 10¹⁷ ат/см³) переважна його бiльшiсть знаходиться у преципiтатах. Їх розчинення починається при ~500 ℃ i наступне охолодження не зменшує концентрацiю електрично активної форми Si. Домiнуючим точковим дефектом є Si+ᶜᵈ, хоча деяка частина його утворює асоцiати (Si+ᶜᵈ V²⁻ᶜᵈ ). Монокристаллы CdTe<Si> были исследованы путем измерениями эффекта Холла под давлением пара Cd в интервале температур 200-900 ℃. На основании экспериментальных результатов предположено, что растворимость Si при 500-600 ℃ меньше, чем ~ 3*10¹⁶ ат/см³. Коэффициент распределения Si в CdTe больше единицы (kₛₑᵣᵍ > 1), что отличает его от других элементов IVA подгруппы. При высоком содержании Si (~ 10¹⁷ ат/см³) большая его часть находится в преципитатах. Их растворение начинается при ~500 ℃ и последующее охлаждение не уменьшает концентрацию электрически активной формы Si. Доминирующим точечным дефектом является Si+ᶜᵈ, хотя некоторая его часть образует ассоциаты (Si+ᶜᵈ V²⁻ᶜᵈ).